Ruzani, Clarry Sada, Uray Salam Prodi Bahasa Inggris, FKIP Universitas Tanjungpura email: ruzani.casanova@gmail.com - Ruzani, .; Sada, Clarry; Salam, Uray (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract: This research is about English Friendly 5 CDâ€™s towards studentsâ€™ vocabulary mastery to the fifth year students of SDS Abdi Agape PontianakThe aim of the present research is to find out whether English Friendly 5 CDâ€™s towards studentsâ€™ vocabulary mastery effective or not.The method of this research was a Pre-experimental Study. The population was 43 students and 20 students of class B was a sample.The technique of data collecting was measurement and the tool of collecting data was a test in form ofÂ a matching test. From the computation, it can be concluded that the teaching of vocabulary through Multimedia of English Friendly 5 CDâ€™swas â€œhighly effectiveâ€. Therefore, the null hypothesis that says â€œEnglish Friendly 5 CDâ€™s was not effective towards studentsâ€™ vocabulary masteryâ€ was rejected. And the alternative hypothesis that says â€œEnglish Friendly 5 CDâ€™s was effective towards studentsâ€™ vocabulary masteryâ€ was accepted. Keywords: vocabulary mastery, Pre-experimental Study, Multimedia Â Abstrak: Penelitian ini adalah tentang English Friendly 5 CDâ€™s terhadap penguasaan kosakata bahasa Inggris untuk siswa tahun kelima SDS Abdi Agape Pontianak Tujuan dari penelitian ini adalah untuk mengetahui apakah English Friendly 5 CDâ€™s berpengaruh terhadap siswa penguasaan kosakata efektif atau tidak . Metode penelitian ini adalah studi Pra-eksperimental. Populasi adalah 43 siswa dan 20 siswa dari kelas B sebagai sampel . Teknik pengumpulan data adalah pengukuran dan alat pengumpulan data adalah tes dalam bentuk tes pencocokan. Dari perhitungan, dapat disimpulkan bahwa pengajaran kosakata melalui Multimedia English Friendly 5 CDâ€™s